A concise review on the Suitability of Nano-Refrigerants for Residential Refrigeration Systems (RRS) - Ikumapayi Omolayo M.; Ogedengbe Temitayo S.; Laseinde Opeyeolu T.; Kazeem Rasaq A.; Afolalu Sunday A.; Ogundipe Adebayo T.; Akinlabi Stephen A.; Akinlabi Esther T. (E3S Web of Conferences, 2023)
Nanoparticles have recently attracted huge attention as an engineering alternative in various fields. This is not unconnected with its established ability to perform better when used to replace some conventional systems or used as an enhancement for the system. Hence, this study reviewed the viability of nanofluids developed from nanoparticles as a possible replacement for conventional refrigerants available. In this review, focus was placed on refrigerants and refrigeration types, Nanoparticles and Nanofluids, Synthesis, Characterization and properties of Nanoparticles and finally on Nano-refrigerants and their viability. Conclusions were reached based on findings of the review.